2016
DOI: 10.4238/gmr15048367
|View full text |Cite
|
Sign up to set email alerts
|

miR-129b suppresses cell proliferation in the human lung cancer cell lines A549 and H1299

Abstract: ABSTRACT. Lung cancer is one of the most prevalent malignant tumors, and is one of the primary causes of cancer-associated deaths. In 2002, an estimated 1.18 million lung cancer-associated deaths were recorded, accounting for 18% of cancer-related deaths and 2% of total mortality. Despite the great progress that has been made in lung cancer therapies, the mechanisms underlying lung cancer formation and development remain largely unknown. Meanwhile, the microRNA miR-129 has been shown to be involved in the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Aberrant expression of miRNAs influences tumorigenic phenotypes, including cell proliferation, the cell cycle, migration, and invasion, thereby accelerating the development of cancer. In NSCLC, aberrant expression of miRNAs is a key regulatory factor underlying carcinogenicity, with miR-204, 14 miR-129b, 15 miR-1298, 16 miR-107, 17 miR-342-3p, 18 and miR-373 19 all having been implicated in previous reports. Here, we demonstrated that miR-647 was highly expressed in tumors that had undergone argon–helium cryoablation treatment, compared with those that had undergone non-argon–helium cryoablation.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of miRNAs influences tumorigenic phenotypes, including cell proliferation, the cell cycle, migration, and invasion, thereby accelerating the development of cancer. In NSCLC, aberrant expression of miRNAs is a key regulatory factor underlying carcinogenicity, with miR-204, 14 miR-129b, 15 miR-1298, 16 miR-107, 17 miR-342-3p, 18 and miR-373 19 all having been implicated in previous reports. Here, we demonstrated that miR-647 was highly expressed in tumors that had undergone argon–helium cryoablation treatment, compared with those that had undergone non-argon–helium cryoablation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the inhibition of miR‐129 could promote tumor formation. For instance, it has been shown that the reduction of miR‐129 could contribute to human lung cancer cell proliferation (Zheng, Qi, Liu, Shi, & Yang, 2016). Therefore, we concluded that miR‐129 may have a significant influence in tumorigenesis, and its roles in READ need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…8 MiR-129-5p is an essential member of miR-129 family. 9 Dysregulation of miR-129 family members has been investigated in various cancers such as human prostate carcinoma, 10 breast cancer, 11 lung cancer, 12 gastric cancer. 13 targeting HMGB1 was reported by Yang et al 15 Xu et al also reported that miR-129-5p inhibited glioblastoma cell viability and metastasis by targeting FNDC3B.…”
mentioning
confidence: 99%